1962
DOI: 10.1017/s0021859600015318
|View full text |Cite
|
Sign up to set email alerts
|

Measuring soluble phosphorus in soils, comparisons of methods, and interpretation of results

Abstract: Soil samples from 179 field experiments testing phosphate fertilizers on potatoes, swedes and grass were analysed for total phosphorus, and for phosphorus soluble in the following solutions: 0·3 N-HCl, 0·002 N-H2SO4, 1% citric acid (H3Ci), 0·5 N acetic acid (HAc), acetic acid-sodium acetate buffer (HAc-NaAc) at pH 4·8, 0·5 M-NaHCO3, and 0·01 M CaCl2.Average values for soluble P were closely related to average crop responses to superphosphate in the experiments on swedes, but not in the grass and potato experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

1963
1963
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 8 publications
(3 reference statements)
0
4
0
Order By: Relevance
“…a n c l Williams & Cooke (1965) showed that extraction with sodium bicarbonate (Olsen et al 1954) Many chemical extractants have been used in was superior to most other extractants they tested, attempts to characterize soils according to their Boyd (1965), summarizing National Agricultural content of plant-available phosphorus (Mattingly& Advisory Service (now Agricultural Development Talibudeen, 1967;Kamprath & Watson, 1980) and and Advisory Service (ADAS)) experiments, their likely response to fresh P fertilizer dressings showed that this method alone, or when allowance (Lorenz & Vittum, 1980). In experiments in was also made for soil type, accounted for between England and Wales, Warren & Johnston (1965) 37 and 50% of the variance of the P responses.…”
Section: Introductionmentioning
confidence: 99%
“…a n c l Williams & Cooke (1965) showed that extraction with sodium bicarbonate (Olsen et al 1954) Many chemical extractants have been used in was superior to most other extractants they tested, attempts to characterize soils according to their Boyd (1965), summarizing National Agricultural content of plant-available phosphorus (Mattingly& Advisory Service (now Agricultural Development Talibudeen, 1967;Kamprath & Watson, 1980) and and Advisory Service (ADAS)) experiments, their likely response to fresh P fertilizer dressings showed that this method alone, or when allowance (Lorenz & Vittum, 1980). In experiments in was also made for soil type, accounted for between England and Wales, Warren & Johnston (1965) 37 and 50% of the variance of the P responses.…”
Section: Introductionmentioning
confidence: 99%
“…Such studies have been reported by many workers for distinct regions. For example, Williams and Cooke (1962) compared eight methods on soils from 179 field trials with phosphate on potatoes, swedes, and grass in England.…”
Section: Introduction 893mentioning
confidence: 99%
“…b e e n d e v e l o P e d and related to crop response, e.g. Williams & Cooke (1962), Tolman, Johnson & The late E. M. Crowther made a comprehensive Gaddie (1956). Olsen et al (1954) used sodium study of the relationship between soil phosphorus bicarbonate solution to extract the ' available' soil and response by sugar beet to phosphate fertilizer phosphorus; this method should be especially suit-(reported by Warren .…”
mentioning
confidence: 99%